2019
DOI: 10.1002/pmrj.12142
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Mild Stroke: A Mapping Review

Abstract: Persons with mild stroke experience motor and cognitive impairments that negatively affect their health and quality of life. To address these deficits, it is essential for clinicians and researchers to precisely identify mild stroke survivors. Despite the fact that half of all strokes are categorized as mild, no standards exist on what constitutes a “mild” stroke. The purpose of this study is to summarize the current classification of mild stroke using a mapping review approach. Strategies to categorize “mild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Since patients with a NIHSS score ≤ 3 had the best short-and medium-term outcome, the authors suggested to use this easily-applicable definition [18]. Although this definition has been used in some studies [19,20], a recent review of this topic reported that the NIHSS-with a score ranging from 0 to 5-is the most commonly used tool to define a "mild stroke" [21]. Similarly, we utilized an NIHSS score of 0 to 5 for identifying patients with supposed "mild" symptoms; our patients had a median NIHSS score of 2.…”
Section: Discussionmentioning
confidence: 99%
“…Since patients with a NIHSS score ≤ 3 had the best short-and medium-term outcome, the authors suggested to use this easily-applicable definition [18]. Although this definition has been used in some studies [19,20], a recent review of this topic reported that the NIHSS-with a score ranging from 0 to 5-is the most commonly used tool to define a "mild stroke" [21]. Similarly, we utilized an NIHSS score of 0 to 5 for identifying patients with supposed "mild" symptoms; our patients had a median NIHSS score of 2.…”
Section: Discussionmentioning
confidence: 99%
“…This finding of better discrimination of EF and GC at the higher end of the mRS may also explain why individuals with strokes often continue their care with untreated cognitive impairments, as previously reported. 42,43 It is possible that implementation of Neuro-QoL measures of EF and/or GC in clinical contexts may help address this shortcoming in patient care, particularly during the first 90 days of recovery. Moreover, implementation of these measures in stroke trials may help uncover differential effects of distinct treatment approaches that may go undetected when using the mRS alone.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A mild stroke (the National Institutes of Health Stroke Scale ≤4 and the modified Rankin Scale 0-1) causes residual infarction, but minimal to no residual physical deficits. 1,3 There is generally no need for rehabilitation services following a TIA or mild stroke. 1,4 Although this patient population is assumed to return to prestroke functional and physical activity capabilities, 1,2,4 evidence shows a long-term risk of recurrent stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Transient ischemic attack (TIA) is a short-lived neurological disturbance resulting from cerebral vascular occlusion 1,2. A mild stroke (the National Institutes of Health Stroke Scale ≤4 and the modified Rankin Scale 0-1) causes residual infarction, but minimal to no residual physical deficits 1,3. There is generally no need for rehabilitation services following a TIA or mild stroke 1,4.…”
Section: Introductionmentioning
confidence: 99%